Knowledge and Experience of Women with Breast Cancer Receiving Chemotherapy in Selected Public Hospitals, Addis Ababa Ethiopia, 2021: Cross-sectional Study - Ayalew, Kalkidan; Ayalew, Yohannes; Alemu, Tsion; Gebru, Tilaye (Asian Pacific Journal of Cancer Care, 2022)
Background: Breast cancer is the most common cancer in women worldwide, in 2018 2.1 million new cases are diagnosed. In Ethiopia due to the increasing awareness of breast cancer patients are taking chemotherapy in different parts of the country but patients’ knowledge of chemotherapy and experience of chemotherapy have not been assessed very well and this study tried to assess patients’ knowledge about chemotherapy. Objective: The objective of the study is to assess the knowledge and experience of women with breast cancer receiving chemotherapy in selected public hospitals in Addis Ababa Ethiopia, in 2021. Methods: Institutional based cross-sectional study was conducted and data was collected from Tikur Anbessa Specialised Hospital and Saint Paul Hospital Millennium Medical College from February 8 to March 1, 2020. Data was entered into Epi-data version 4.6.0 and exported to SPSS version 26. Descriptive statics such as frequency, percentages, mean and standard deviation were done and displayed in tables. Bivariate and multivariate logistic regression analysis was employed. Results: The study involved 250 participants. The mean age of the respondents was (43.35±11.1). Of the total 135 (54%) respondents were not knowledgeable and 115 (46%) were knowledgeable. Age >45 years and patients who lived in Addis Ababa were associated with higher knowledge. Respondents who took chemotherapy fourth to the sixth cycle and who are currently single were associated with the worst experience and the distance-time it takes to get to the hospital when is three to six hours were associated with the tolerable experience. Conclusion and recommendations: The study revealed that more than half of the participants were not knowledgeable and more than half of the participants had the worst experience. Hence healthcare providers should provide information about chemotherapy to their patients and should teach them how to manage the possible side effects.